Aṭṭhasālinīaṭṭhakathānisya - Buddhaghosa (Jambūʹ Mitʻ chve Piṭakatʻ Puṃ nhipʻ Tuikʻ, 1939)
Burmese paraphrase of Buddhaghosa's commentary on Dhammasaṅgaṇi, section of Abhidhammapiṭaka, canonical text of Theravada Buddhism.